(3ELGHGJ Yf eSGFd hQOJ HUYOI ef GdCejQ eLO GdOjf jMji Hf eMeO Hf GdgGOi Edi GdMbs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3hbafG Ydi cJGH GdCejQ GdCLd GdChMO Gdecjf eLO GdOjf COGe Gddg Ydhg heG bQQ ajg ef GdNeS GdeSGFd s
(3BNQgG (B:s
(3GdLhGH Cf gPG ZjH CNHQfG Gddg Hg , hgh YdGe GdZjhH , hdPdc hgh Mcje Ydje , hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3cJHJ HYV GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis